Answer:
x = - 3, y = - 1
Step-by-step explanation:
y = 7x + 20 -----> equation 1
4x - y = - 11
4x - ( 7x + 20 ) = - 11
4x - 7x - 20 = - 11
- 3x = - 11 + 20
- 3x = 9
x = 9 / - 3
x = - 3
Substitute x = - 3 in equation 1,
y = 7 ( - 3 ) + 20
= - 21 + 20
y = - 1
Hence,
x = - 3
y = - 1
Answer:
<h3>
34, 35</h3>
Step-by-step explanation:
z - some integer
then the consecutive integer would be:
z+1, (or z-1)
the sum is 69 so:
z + z+1 = 96
2z = 68
z = 34
z+1 = 34 + 1 = 35
(or:
z + z-1 = 69
2z = 70
z = 35
z-1 = 35 - 1 = 34)
The rule is plus four because every time you take your x value and add four it equals your y value.
Um idk sorry lol that’s way to hard for me
I think it’s A because it matches with the graph